Assessing the Knowledge, Attitude and Practice of Emergency Contraceptives among Females Attending Feminine and Children Teaching Hospital in Al- Samawah City - Jasim, Enas Yassen (International Journal of Psychosocial Rehabilitation, 2020)
Background: Emergency contraception is important in inhibiting unintended pregnancy. Knowledge of females regarding emergency contraception is essential in preventing many maternal morbidity and mortality.Aim of study: To assess the level of knowledge towards emergency contraception in a group of women attending Al-Samawah Feminine and children Teaching Hospital.Patients & Methods: A cross sectional study conducted in Consultancy Clinic of Feminine and children teaching hospital in Al-Samawa city-Iraq through the period from 1st of January, to 31st of December, 2019 on sample of 300 females. The data were collected by the researchers directly from selected females and fulfilling a prepared questionnaire.Results: From the total 60 (20%) females with positive knowledge about emergency contraception. Hearing about emergency contraception was significantly related to increased age, higher educational level, employed females and urban residency. The occupation of females was significantly related to type of emergency contraception. History of previously using the emergency contraception was significantly related to age and educational level of females.Conclusions: The knowledge of females attended Consultancy Clinic of Feminine and children Teaching Hospital regarding emergency contraception was low.